Sustainable Supply Chain Management and Firm Performance in Ghana: Examining the Mediating and Moderating Factors - Asante-Darko, Disraeli (University of the Witwatersrand, Johannesburg, 2022)
In the wake of increasing environmental degradation and human rights violations and their effect on firm performance in Ghana and the rest of the world, sustainable supply chain management has increasingly become recognised as a critical component for business advancement and competitiveness. Subsequently, this study sought to investigate the role of Supply Chain Integration, Firm Capabilities, Business Environment Uncertainty, and Operational Competitiveness in the inextricable relationship between Sustainable Supply Chain Management (SSCM) and firm performance. Drawing on the political economy theory, an integration of institutional, legitimacy, and stakeholder theories, this study proposed and tested a model using the PLS variance-based structural equation modelling. The proposed model suggested that the relationship between sustainable supply chain management and firm performance, from a triple bottom line (TBL) perspective, is mediated by firm capabilities and supply chain integration and moderated by business environment uncertainty and operational competitiveness. Grounded in deductive reasoning and a probabilistic sampling technique, the study adopted a cross-sectional quantitative approach to evaluate the proposed model. Data was collected from the managers of 455 sample firms in Ghana's service and industrial sectors using a self-administered questionnaire. From a TBL perspective, the study revealed a direct, positive, and significant relationship between sustainable supply chain management and firm performance. Additionally, firm capabilities mediate the relationship between sustainable supply chain management and firm performance from a TBL standpoint. Supplier integration, a component of supply chain integration, was also found to mediate the relationship between economic and environmental supply chain management and firm performance but not the relationship between social supply chain management and firm performance. It further emerged that customer and internal integration mediate the relationship between sustainable supply chain management and firm performance. Finally, the study discovered that when business environment uncertainty and operational competitiveness are high, the positive direct effect of sustainable supply chain management on firm performance (from a TBL standpoint) is strengthened. The study's findings provide a plausible explanation for the disparate and often contradictory results reported on the direct sustainable supply chain management-firm performance relationship. The theoretical implication is that multiple variables and elements account for the SSCM-firm performance relationship. There is a need to adequately address these factors to realise the full benefits of sustainable supply chain management and firm relationships from a TBL perspective. SSCM practitioners and policymakers are advised to take cognisance of the role of supply chain integration, firm capabilities, business environment uncertainty, and operational competitiveness in their implementation and legislation of SSCM practices
A thesis submitted to the Faculty of Commerce, Law, and Management, The University of the Witwatersrand, in partial fulfillment of the requirements for the degree of PhD in Management, Johannesburg 2022
Keywords: Sustainable supply chain management; Firm performance; Supply chain Integration; Business environment uncertainty; Operational competitiveness; Firm capabilities; Ghana; UCTD; SDG-8: Decent work and economic growth